Comparison of Forelimb and Hindlimb Systolic Blood Pressures and Proteinuria in Healthy Shetland Sheepdogs - Scansen, B.A. (J Vet Intern Med, 2014)
BACKGROUND: The prevalence of systemic hypertension (SHT) in Shetland Sheepdogs has not been reported. HYPOTHESIS/OBJECTIVES: SHT is common in Shetland Sheepdogs and positively correlated with proteinuria. Measurements of forelimb and hindlimb systolic arterial pressure (SAP) are comparable. ANIMALS: Seventy‐two clinically healthy, client‐owned Shetland Sheepdogs. METHODS: Forelimb and hindlimb SAP were recorded by Doppler ultrasonography. Proteinuria was quantified by urine dipstick, microalbuminuria, and protein:creatinine ratio (UPC). The relationship of UPC, anxiety, age, weight, and heart rate with forelimb SAP was evaluated. RESULTS: The mean forelimb and hindlimb SAP were 132 ± 20 and 118 ± 20 mmHg, respectively. The SAP exceeded 160 mmHg in 9 dogs, suggesting 13% prevalence of SHT. Four dogs had a UPC above 0.5; 2 of these had forelimb SAP exceeding 160 mmHg. Correlation of forelimb and hindlimb SAP was poor (r (2) = 0.09; P = .011). Bland–Altman plots revealed substantial bias (−14 mmHg) between limb measurements with clinically unacceptable 95% limits of agreement (−60 to 33 mmHg). There was no correlation between forelimb SAP and UPC (P = .06) or anxiety level (P = .49). Age (P < .0001) and heart rate (P = .038) were significant predictors of forelimb SAP; weight (P = .73) was not. CONCLUSIONS: Prevalence of SHT was 13% and not correlated with proteinuria. Forelimb and hindlimb SAP were poorly correlated; therefore, trends in an individual animal should be monitored using the same measurement site. Additionally, values for Doppler SAP were determined in Shetland Sheepdogs.